2017
DOI: 10.1080/00207454.2017.1377709
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Rosai–Dorfman disease with central nervous system involvement

Abstract: Rosai-Dorfman disease (RDD) is a rare idiopathic and lymphoproliferative disorder. Central nervous system (CNS) involvement is infrequent and typically manifests as an isolated lesion. In this article, we describe an unusual case of RDD with multiple lesions in the CNS, upper respiratory tract and lymph nodes. A literature review revealed 45 cases (including the one described herein) of systemic RDD with CNS involvement documented to date. Among these cases, 29 (64.4%) presented with intracranial lesions, 10 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…[199] Regarding to the neuroimaging, the best diagnostic clues for diagnosing CNS-RDD appear to be represented by hypo-isointensity in the T2-weighted sequences and the relatively low rCBV perfusion values, likely due to abundant fibrous tissue; however, these findings are not specific and not always present, and the final diagnosis is often still histological. [199] erefore, preoperative radiological findings using current MRI sequences are difficult to distinguish between meningiomas and RDD; however, it has already been described that the absence of hyperostosis, bony erosion, or calcification -characteristically absent in the RDD [177] -should suggest RDD as a differential diagnosis of meningiomas. [150] As for the two reported cases of RDD, they were very similar to the expected age group and sex grouping, according to the literature and our review.…”
Section: Discussionmentioning
confidence: 99%
“…[199] Regarding to the neuroimaging, the best diagnostic clues for diagnosing CNS-RDD appear to be represented by hypo-isointensity in the T2-weighted sequences and the relatively low rCBV perfusion values, likely due to abundant fibrous tissue; however, these findings are not specific and not always present, and the final diagnosis is often still histological. [199] erefore, preoperative radiological findings using current MRI sequences are difficult to distinguish between meningiomas and RDD; however, it has already been described that the absence of hyperostosis, bony erosion, or calcification -characteristically absent in the RDD [177] -should suggest RDD as a differential diagnosis of meningiomas. [150] As for the two reported cases of RDD, they were very similar to the expected age group and sex grouping, according to the literature and our review.…”
Section: Discussionmentioning
confidence: 99%
“…Its clinical presentation is very heterogenous and depends on the affected body sites, but it usually presents with bilateral, massive and painless cervical lymphadenopathy that might be associated with fever, weight loss, night sweats, polyclonal hypergammaglobulinemia, high erythrocyte sedimentation rate and leukocytosis [ 5 9 , 15 ]. The most common extra-nodal sites are skin, orbit and eyelid, bone, central nervous system and upper respiratory tract [ 5 – 7 , 11 , 15 – 17 ]. Biopsy reveals accumulation of histiocytes positive for S-100 protein and for CD 68, and negative for CD1a on immunohistochemical examination [ 5 – 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the absence of internal calcification or haemorrhage on CT and the presence of areas of low intensity within the lesion on T2-weighted MRI can help in differentiating meningeal RDD from a meningioma [ 19 , 20 ]. It may also eventually resemble lymphomas or metastases and biopsy is necessary for a histopathological diagnosis to be confirmed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, MRI imaging of RDD are often more difficult to distinguish from other more frequently encountered extradural spinal lesions, including meningioma, metastases, lymphoma and plasma cell granuloma. [ 6 , 13 ] Meningioma and RDD share similar features such as homogenous contrast enhancement in a dural-based lesion, although meningiomas typically have the distinct dural tail sign. Metastases are often T1WI hypo-intense and T2WI hyper-intense.…”
Section: Discussionmentioning
confidence: 99%